Risk of perioperative coronary stent stenosis or occlusion in patients with previous percutaneous coronary intervention undergoing coronary artery bypass grafting surgery. (3rd February 2020) - Grieshaber, Philippe; Oswald, Irina; Albert, Marc; Reents, Wilko; Zacher, Michael; Roth, Peter; Niemann, Bernd; Dörr, Oliver; Krüger, Tobias; Nef, Holger; Sodah, Ayman; Hamm, Christian; et al.
Abstract: OBJECTIVES: There is an ongoing discussion about how to treat coronary stents during bypass surgery: Should patent stents be left alone and the stented vessels be ungrafted, or should every stented coronary artery receive a bypass graft? This study aims to determine the relevance of perioperative stent stenosis or occlusion on postoperative outcomes up to 3 years postoperatively. METHODS: Patients undergoing coronary artery bypass grafting surgery (CABG) (±concomitant procedures) with previous percutaneous coronary intervention from 4 centres were prospectively included in this observatory study between April 2015 and June 2017. A coronary angiography was conducted between the fifth and seventh postoperative days. The preoperative and postoperative angiograms were assessed in a core laboratory, assessing the patencies of coronary stents and bypass grafts. The core lab investigators were blinded to the patients' characteristics and perioperative course. RESULTS: A total of 107 patients were included in the study. In the postoperative coronary angiography, 265 bypass grafts and 189 coronary stents were examined angiographically. Ninety-seven percent of preoperatively patent stents remained patent. New coronary stent stenoses were observed in 5 patients (4.7%). All 5 patients were asymptomatic and managed conservatively. Bypass stenoses were observed in 12 patients (11%), of whom were managed conservatively, 4 underwent percutaneous coronary intervention and 1 underwent redo-CABG. Two years postoperatively, 97% of patients were alive. Patients with new stent stenosis tended to have a better survival compared with patients with bypass stenosis (100% vs 73%; P  = 0.09) up to 3 years postoperatively. CONCLUSIONS: Perioperative coronary stent stenosis occurs rarely. It is safe to leave a patently stented coronary vessel without bypass grafting.